Modelling and Vibration Control of Planar Systems by the Use of Piezoelectric Actuators - LENIOWSKA, Lucyna (Archives of Acoustics, 2009)
n recent years, a great deal of work has been done on the development of control methodologies for structural and acoustic applications by using piezoelectric actuators. This paper presents the derivation of the models for planar structures with surface-mounted piezoelectric actuators. In the first approach, a parametric system identification procedure is employed to establish a mathematical model of the considered system, on the basis of the data collected from the measurements. The second approach consist in modelling of the fluid-acoustic-structural dynamics in the form of the partial differential equations, derived from physical principles such as forces and moments balance. Assuming axially symmetrical vibrations, on the basis of the models derived, the control algorithm has been developed for the circular plate to which centrally placed PZT actuators were bonded. The results of performed simulations are included and discussed.